Murder at Gulls Nest - Kidd, Jess (Kidd, Jess. Nora Breen investigates., 2025)
"From Jess Kidd, the bestselling author of Things in Jars who "is so good it isn't fair" (Erika Swyler, nationally bestselling author), the first in a cozy mystery series about a former nun who searches for answers in a small seaside town after her pen pal mysteriously disappears. I believe every one of us at Gulls Nest is concealing some kind of secret. 1954: When her former novice's dependable letters stop, Nora Breen asks to be released from her vows. Haunted by a line in Frieda's letter, Nora arrives at Gulls Nest, a charming hotel in Gore-on-Sea in Kent. A seaside town, a place of fresh air and relaxed constraints, is the perfect place for a new start. Nora hides her identity and pries into the lives of her fellow guests. But when a series of bizarre murders rattles the occupants of Gulls Nest it's time to ask if a dark past can ever really be left behind."--